1998
DOI: 10.2307/176522
|View full text |Cite
|
Sign up to set email alerts
|

Population Growth of Antarctic Fur Seals: Limitation by a Top Predator, the Leopard Seal?

Abstract: Abstract. Antarctic fur seals (Arctocephalus gazella) in the South Shetland Islands are recovering from 19th-century exploitation more slowly than the main population at South Georgia. To document demographic changes associated with the recovery in the South Shetlands, we monitored fur seal abundance and reproduction in the vicinity of Elephant Island during austral summers from 1986/1987 through 1994/1995. Total births, mean and variance of birth dates, and average daily mortality rates were estimated from da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 39 publications
0
39
0
Order By: Relevance
“…The possible cost of migration can be manifested either as lower survival or lower fecundity. Survival costs are usually due to predation (Boveng et al . 1998).…”
Section: Methodsmentioning
confidence: 99%
“…The possible cost of migration can be manifested either as lower survival or lower fecundity. Survival costs are usually due to predation (Boveng et al . 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Although the pup and the juvenile are attacked by predators such as leopard seals (Hydrurga leptonyx; Boveng et al 1998, the adult is under lower predation risk. This is a challenging species in which to study foraging because foraging itself cannot be observed directly, but this is compensated by other features of its biology.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality of seal pups due to catastrophic meteorological events varies with the topographic characteristics of the haulout area (Le Boeuf and Briggs 1977, Riedman and Le Boeuf 1982, Doidge et al 1984, Boveng et al 1998, Baker et al 2006; some rookeries experience very little mortality during storms because the topography of the haulout area provides adequate protection (de Villiers and Roux 1992, Pemberton and Kirkwood 1994, Boveng et al 1998, Gucu et al 2004. By contrast, Black Rocks is low-lying and offers very little protection during storms.…”
Section: Discussionmentioning
confidence: 99%